Prevalence of sexual abuse of male high school students in Addis Ababa, Ethiopia - Haile, Rahel Tesfaye (BioMed Central, 2013)
BACKGROUND: Sexual abuse of boys is a neglected problem in many developing countries including Ethiopia. As a result, its prevalence, contributing factors and circumstance in which sexual abuse occurs are largely unknown. The objective of this study is to determine the prevalence and factors associated with sexual abuse of male high school students in Addis Ababa city administration. METHODS: A cross-sectional descriptive study involving 884 randomly selected students of nine high schools in Addis Ababa was conducted in March 2009. A pre-tested questionnaire was used to collect data. Analysis of the data was made using SPSS for windows version 15. RESULTS: This study indicates the life time prevalence of rape and sexual harassment of boys in Addis Ababa were 4.3%, and 68.2%, respectively. The chance of experiencing sexual coercion was higher among students who live alone (AOR = 2.87; 95% CI; 1.07, 7.66) and among students who live with others (AOR =1.80; 95% CI = 1.04, 3.11) than those living with both parents. Similarly, the odds of experiencing rape in their life time was higher among students who live with others (AOR=2.20; 95% CI; 1.04, 4.68) than those who live with their parents. CONCLUSIONS: Sexual abuse of male students is not uncommon in Addis Ababa. It is higher in those living alone or not living with their parents. Due attention is needed by schools, parents and other concerned bodies. Designing a program to fight against sexual abuse should include young school boys.